A simple mechanical model for simulating cross-country skiing, skating technique. Issue 2 (June 2016) - Bruzzo, John; Schwab, A.; Valkeapää, Antti; Mikkola, Aki; Ohtonen, Olli; Linnamo, Vesa
Abstract The role of simulation models in sport disciplines has become relevant lately due to the multiple advantages that they may offer sports teams, coaches and practitioners. This paper develops and presents a simple three-dimensional multibody dynamic model of a cross-country skier, modeling a single propulsion phase to obtain the kinetic parameters involved in the movement. A professional Olympic-level skier performed the skating technique without poles in a ski tunnel under controlled conditions and on an incline plane. Then, with a force acquisition system attached to the ski bindings and a motion capture system set on site, the leg resultant forces and the movement of specific points of the skier's lower body were acquired. The data obtained from the motion capture system were used as the prescribed kinematic input data in the multibody model and the measured force was used later as a parameter of comparison with the results of the simple model. After simulating the technique, the calculated resultant forces seem to be in agreement with those measured in the field.